Changing the Face of Multicultural Counselling with Principles of Change - Daya, Roshni (Canadian Journal of Counselling and Psychotherapy, 2007)
Discussion in multicultural counselling has focused on whether the culture specific (emic) or universal position (etic) is more useful. More recently a common factors approach has been introduced. This article provides a critical analysis of each of these positions and introduces the principles of change approach as a way of unifying multicultural counselling and moving the conversation to a more applied level. Directions for future research are provided.